A Narrative Review on Exercise and Cardiovascular Events: “Primum Non Nocere” - Kyriakos Dimitriadis; Evanthia Bletsa; Emilia Lazarou; Ioannis Leontsinis; Panagiota Stampouloglou; Eirini Dri; Athanasios Sakalidis; Nikolaos Pyrpyris; Panagiotis Tsioufis; Gerasimos Siasos; Dimitrios Tsiachris; Konstantinos Tsioufis (Heart and Mind, 2022)
Exercise provides beneficial effects on the primary and secondary prevention of numerous chronic conditions, including cardiovascular disease, diabetes mellitus, and malignancies. Despite its indisputable benefits, exercise can rarely trigger major adverse cardiovascular events such as ventricular arr hythmias, myocardial infarction, or even sudden cardiac arrest in susceptible individuals. Physiological changes that occur during exercise, including increased sympathetic activity and cardiac oxygen requirements, may account for ischemia and trigger ventricular ectopy with eventually adverse outcomes. Tailored preparticipation screening for exercise and sports engagement is fundamental to unveiling underlying pathological conditions. The present review summarizes the overall impact of exercise on cardiovascular health and highlights the recommended prevention strategies.